Comparison of the Effects of Two Types of Gait-Retraining Approach on the Balance and Motor Performance of Elderly Women at Risk of Falling - Mahnaz Abdullah Chalaki; Mohammad Karimizadeh Ardakani; Karim Khalaghi Birak Olia (Shahid Beheshti University of Medical Sciences, 2022)
Background and Aims Aging causes alterations in various body functions, such as motor, sensory, cognitive and psychosocial. The present study was performed to compare the effects of two types of gait-retraining approach on the balance and motor performance of elderly women at risk of fallingMethods This study is a semi experimental research with pretest-posttest plan, in which 45 women elderly between 60 and 75 years were randomly divided into two experimental (n=30) and  one control groups (n=15). The experimental group (8 weeks, 3 sessions per week, each session 45 minutes). In order to assess on balance and motor performance of subject, Berg Balance Scale, and 10 meter walk test was used. Analysis of covariance (ANCOVA) was used to analyze the data, SPSS statistical package was used for all analyzes. In this study, significance level equal was considered to 95% and level of alpha was considered less than or equal to 0/05.Results The findings of this study showed that both selected exercises had significance effect on balance and motor performance in non reactive elderly women. Conducting a between-group comparison also showed that the which was related to the training with ground balance ladder, respectively (P≤0.05). However, there was no significant difference in the control group for all three variables.Conclusion This study showed that exercise two kinds of tutorial gait approach reduce can improve postural control and decrease the risk of falls in the elderly. Therefore it can be used to reduce risk of falls.